Analisis Value terhadap Minat Penggunaan MyTelkomsel menggunakan Consumption Value Model - Ailsa Nabila Irvhan; Satrio Hadi Wijoyo; Andi Reza Perdanakusuma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
The purpose of this research is to know the value that is felt by users that influence the interest in using MyTelkomsel. The population in this research is users of MyTelkomsel in Malang with the sampling using sampling purposive with 100 respondents. The data sampling of this research is done by spreading questionnaires. Data analysis is done using classic assumption test, partial test, and multiple regression analysis to five variables which is, functional values, emotional values, epistemic values, conditional values, and social values. Pearson correlation test was also conducted to determine the closeness of the relationship between these variables with the intention to use variable. Testing is done using SPSS tools. The conclusion from the results of the research conducted showed that functional values variables, emotional values variables, and social values variables have a significant positive influence on the interest in using the MyTelkomsel application with an enough closeness relationship while the epistemic values variable does not significantly influence the interest in using the MyTelkomsel application with the closeness of the relationship low or weak, and conditional values variables also have no significant effect on the interest in using the MyTelkomsel application with a very low or very weak relationship.